Radiographic assessment of endodontic working length - Osama S Alothmani; Lara T Friedlander; Nicholas P Chandler (Wolters Kluwer Medknow Publications, 2013)
The use of radiographs for working length determination is usual practice in endodontics. Exposing radiographs following the principles of the paralleling technique allows more accurate length determination compared to the bisecting-angle method. However, it has been reported that up to 28.5% of cases can have the file tip extending beyond the confines of the root canals despite an acceptable radiographic appearance. The accuracy of radiographic working length determination could be affected by the location of the apical foramen, tooth type, canal curvature and superimposition of surrounding structures. Variations among observers by virtue of training and experience may also influence the accuracy of the procedure. The interpretation of radiographs could be affected by film speed and viewing conditions, with the superiority of digital imaging over conventional radiography for working length determination remaining debatable. The combination of several methods is recommended for acquiring the most accurate working length.